Respuesta :
-31 - 4x = 5 - 5 ( 1 + 5x )
-31 - 4x = 5 - 5 - 25x
-31 - 4x = -25x
+ 31 to both sides
-4x = 6
/ -4 to both sides
x = 6/-4 = 3/-2
-31 - 4x = 5 - 5 - 25x
-31 - 4x = -25x
+ 31 to both sides
-4x = 6
/ -4 to both sides
x = 6/-4 = 3/-2
Let's solve your equation step-by-step.−31−4x=−5−5(1+5x)Step 1: Simplify both sides of the equation.−31−4x=−5−5(1+5x)−31+−4x=−5+(−5)(1)+(−5)(5x)(Distribute)−31+−4x=−5+−5+−25x−4x−31=(−25x)+(−5+−5)(Combine Like Terms)−4x−31=−25x+−10−4x−31=−25x−10Step 2: Add 25x to both sides.−4x−31+25x=−25x−10+25x21x−31=−10Step 3: Add 31 to both sides.21x−31+31=−10+3121x=21Step 4: Divide both sides by 21.21x21=2121x=1